Evaluation of Contribution Zakat for Productive in Destination Mustahik Economic Empowerment in post the Covid-19 pandemic - Izzun Khoirun Nisa (NUsantara Islamic Economic Journal, 2023)
Society loses profession consequence the Covid-19 pandemic , and more people is now live in poverty . Zakat is one from it's Islamic pillar worry with alleviation poverty , in particular in form expenditure productive . It destination from this research is to recognize and judge that mechanisms and contributions from earning zakat to economical Empowerment mustahik During it's the covid-19 pandemic . Zakat for destination productive is possible wealth _ recipient Keep going be creative using zakat funds. this study conducted in a manner deep Interview with three employee zakat institutions and seven mustahik living in the community earn low and _ economy caught impact of covid-19. Study this use method descriptive , with deep data retrieval study this use method interview , continued with data analysis in the form of data reduction , data presentation , and conclusions . According to to that findings from this learn , there is permanent a limited number from Man Source power available for mustahik coaching and supervision at LAZISMU Pemalang . This paper has find that no all mustahik use 100 percent from productive zakat funds for develop effort in accordance hope , however precisely Fulfill needs base need . Mustahik especially need more many fulfillment with benefit period short order for maintain life them .